2019
DOI: 10.5888/pcd16.180362
|View full text |Cite
|
Sign up to set email alerts
|

State-Specific Patterns of Cigarette Smoking, Smokeless Tobacco Use, and E-Cigarette Use Among Adults — United States, 2016

Abstract: Introduction State-level monitoring of changes in tobacco product use can help inform tobacco control policy and practice. This study examined state-specific prevalence of cigarette, smokeless tobacco, and e-cigarette use among US adults. Methods Data came from the 2016 Behavioral Risk Factor Surveillance System (BRFSS), a state-based telephone survey of US adults aged 18 years or older (N = 477,665). Prevalence estimates for current (every day or some days) cigarette s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

5
33
1

Year Published

2019
2019
2024
2024

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 44 publications
(39 citation statements)
references
References 23 publications
5
33
1
Order By: Relevance
“…Previous studies found differences in employee tobacco use, including use of e-cigarettes, by sociodemographic characteristics such as sex and race (8,9). Tobacco use also varies by state (10,11). Our study explored the prevalence and determinants of type of tobacco use (cigarette-only, e-cigarette-only, and dual) among US adult employees to better understand their relationship with sociodemographic characteristics and employment type.…”
Section: Introductionmentioning
confidence: 97%
“…Previous studies found differences in employee tobacco use, including use of e-cigarettes, by sociodemographic characteristics such as sex and race (8,9). Tobacco use also varies by state (10,11). Our study explored the prevalence and determinants of type of tobacco use (cigarette-only, e-cigarette-only, and dual) among US adult employees to better understand their relationship with sociodemographic characteristics and employment type.…”
Section: Introductionmentioning
confidence: 97%
“…The Behavioral Risk Factor Surveillance System (BRFSS) found that Kentucky SLT prevalence was 7.6% (almost 14% among males) 1 in 2017 compared to the 4.1% national average. [6][7][8] Also, any past-30 day use of SLT products among Kentucky high schoolers was estimated at 10.6% in 2017, with the national average rate at 5.5%. 9 While much of SLT use takes the traditional forms of snuff and chewing tobacco, new forms of smokeless, such as different varieties of snus and other oral tobacco products, have also become available in recent years.…”
Section: Introductionmentioning
confidence: 99%
“…E-cigarette (e-cig) usage has become widely prevalent in the U.S. and other countries. There is considerable controversy as to the potential cancer risks and benefits posed by e-cigs [1,2]. Although studies on e-cig liquids, aerosols and condensates have indicated that they contain much lower levels of known carcinogens than tobacco or tobacco smoke [3], there is little reported research on the effects of e-cig usage on cancer risk in current tobacco users (dual users).…”
Section: Introductionmentioning
confidence: 99%